Tear Cytokine Profiles in Dysfunctional Tear Syndrome - Lam, Helene (2008)
PURPOSE: to compare tear cytokine and chemokine concentrations in asymptomatic control and dysfunctional tear syndrome (DTS) patients and determine the correlations between tear inflammatory mediators and clinical severity. DESIGN: Prospective observational cohort study METHODS: Concentrations of epidermal growth factor (EGF), interleukin (IL) - 1α, 1β, 6, 10, 12 and 13, interferon gamma (IFN-γ), tumor necrosis factor alpha (TNF-α) and chemokines: IL-8 (CXC), MIP-1α (CCL3) and RANTES (CCL5) were measured by a multiplex immunobead assay in an asymptomatic control group and DTS patients with and without MGD. Spearman correlations between tear cytokines and severity of irritation symptoms and ocular surface signs were calculated. RESULTS: Tear concentrations of IL-6, IL-8 and TNF-α were significantly higher in DTS with and without MGD and EGF was significantly reduced in the DTS without MGD group compared to the control group. MIP-1α was greater in entire DTS and DTS without MGD groups than the control group and RANTES was greater in DTS with MGD than the control and DTS without MGD groups. IL-12 was significantly higher in the DTS with MGD than the DTS without MGD subgroup. Significant correlations were observed between IL-6 and irritation symptoms and between a number of cytokines and chemokines and clinical parameters. CONCLUSIONS: As predicted, patients with DTS have higher levels of inflammatory mediators in their tears that show correlation with clinical disease parameters. Furthermore, different tear cytokine/chemokine profiles were observed in DTS patients with and without MGD groups.